Migration and imperfect labor markets: Theory and cross-country evidence from Denmark, Germany and the UK - Herbert Brücker; Elke J. Jahn; Richard Upward (Institute for the Study of Labor (IZA), 2012)
We investigate the labor market effects of immigration in Denmark, Germany and the UK, three countries which are characterized by considerable differences in labor market institutions and welfare states. Institutions such as collective bargaining, minimum wages, employment protection and unemployment benefits affect the way in which wages respond to labor supply shocks, and, hence, the labor market effects of immigration. We employ a wage-setting approach which assumes that wages decline with the unemployment rate, albeit imperfectly. We find that wage flexibility is substantially higher in the UK compared to Germany and, in particular, Denmark. As a consequence, immigration has a much larger effect on the unemployment rate in Germany and Denmark, while the wage effects are larger in the UK. Moreover, the elasticity of substitution between natives and foreign workers is high in the UK and particularly low in Germany. Thus, the preexisting foreign labor force suffers more from further immigration in Germany than in the UK.
Keywords: F22; J31; J61; 330; immigration; unemployment; wages; labor markets; panel data; comparative studies; Einwanderung; Internationale Arbeitsmobilität; Lohnverhandlungen; Arbeitsmarktflexibilität; Arbeitslosigkeit; Lohn; Bevölkerung; Vergleich; Deutschland; Dänemark; Großbritannien